We will discuss about the different properties of surds.
If a and b are both rationals and √x and √y are both surds and a + √x = b + √y then a = b and x = y
If a not equal to b, let us assume, b = a + m, where m (m ≠ 0) is a rational.
Now, by question, a + √x = b + √y
⇒ a + √x = a + m + √y
⇒ √x = m + √y, which is impossible (since a simple quadratic surd cannot be equal to the sum of a rational quantity and a simple quadratic surd).
Therefore, we must have, a = b.
When a = b then a + √x = b + √y ⇒ √x = √y ⇒ x = y.
Notes:
1. If a - √x = b - √y where a, b are both rationals and √x, √y are both surds, then proceeding as above we can show a = b and x = y.
2. If √x and √y are actually rationals (in the form of surds), then the relation a + √x = b + √y does not imply a = b and x = y.
For example, we have,
10 = 6 + 4 = 6 + √16 and 10 = 4 + 6 = 4 + √36
⇒ 6 + √16 = 4 + √36
Evidently we cannot have, 6 = 4 or 16 = 36.
This is due to the fact that √16 and √36 are not surds, they represent rational numbers.
3. If a + √x = b + √y where a, b are both rationals and √x, √y are both surds then, a = b i.e. rational parts of two sides are equal and x = y i.e., irrational parts of two sides are equal.
4. If a - √x = b - √y where a, b are both rationals and √x, √y are both surds then, a = b i.e. rational parts of two sides are equal and x = y i.e., irrational parts of two sides are equal.
5. If a + √x = 0, then a = 0 and x = 0.
6. If a - √x = 0, then a = 0 and x = 0.
7. If a + √x = b + √y then, a - √x = b - √y
8. If √(a + √x) = √b + √y then √(a - √x) = √b - √y
9. Identically, if √(a - √x) = √b - √y then √(a - √x) = √b - √y.
11 and 12 Grade Math
From Properties of Surds to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Dec 01, 23 01:16 AM
Nov 30, 23 10:59 PM
Nov 30, 23 01:08 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.